The Effect of Class Management and Identity Crisis on Class 7 of Students’ Behavior Digression at Junior High School in Sambas District - Juni Hartono; Aswandi Aswandi; Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2019)
Students' behavior digression can be caused by factors that originate in students who are experiencing an identity crisis or teacher classroom management in the class is less effective. This study aims to describe the effect of class management and identity crisis together on behavior digression of class VII ( 7th Grade) students in the state junior high school class in Subrayon 4 Tebas, Sambas District. The research method used is descriptive expost method, with a quantitative research approach. The population in this study were all public junior high school teachers in Subrayon 4 Tebas, Sambas District as many as 174 people and the samples were taken by random sampling. The data needed in this study are in the form of questionnaires regarding class management, student identity crisis, and behavior digression of state junior high school students in Subrayon 4 Tebas, Sambas District. The data sources in this study were primary sources (through respondents) and secondary (through documents) consisting of teachers who taught at State Junior High School in Subrayon 4 Tebas of  Sambas District, students who sat in class VII of state junior high school in Subrayon 4 Tebas of Sambas District, the results of data from BP teacher and homeroom teacher. The data collection technique chosen in this study was using indirect communication techniques with a data collection tool using closed questionnaires. The results of the research obtained are (1) teacher class management influences student behavior digression; (2) there is significant influence between student identity crisis and behavior digression; (3) there is a jointly significant relationship between teacher class management variables and student identity crisis towards student behavior digression. Based on the results of the research conducted, it can be concluded that teacher classroom management and student identity crisis significantly influence students' behavioral deviations in the class VII of state junior high school in Subrayon 4 Tebas, Sambas District.